-7(-6x+8)=238

Simple and best practice solution for -7(-6x+8)=238 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-6x+8)=238 equation:



-7(-6x+8)=238
We move all terms to the left:
-7(-6x+8)-(238)=0
We multiply parentheses
42x-56-238=0
We add all the numbers together, and all the variables
42x-294=0
We move all terms containing x to the left, all other terms to the right
42x=294
x=294/42
x=7

See similar equations:

| 4+2.2.h=-3.7 | | -8(7a-3)=-256 | | 3x-16+103=180 | | 3x+8x-167=53 | | (2x-30+30)/2=180-x | | -2x-86+12x=164 | | 14.2=11.6+2x | | 9x/8=4x+7 | | 5x+24-3x=-6 | | -50-4x+9x=65 | | 14.2=-5.8+x | | 9x8=4x+7 | | x^2-5x=-12+8x | | 16=1-2x+5x+3 | | 15x-11=13x-7 | | -25=-4x-6x+5 | | 2k+3=28 | | h/7-4=1 | | 3x+5=5x+1 | | 2x=14.68 | | 3a+25=67 | | 3/x+8=11 | | 13x-43+13=66 | | b=6b-2 | | 8-7/8=x | | y+1.60=12.6 | | y+12.6=1.60 | | 100f=(.27)(100)100f= | | y-12.6=1.60 | | -3(2+6m)=-6(m-1) | | y-1.60=12.6 | | 0.29y=3.19 |

Equations solver categories